2023
DOI: 10.1021/jacs.2c10932
|View full text |Cite
|
Sign up to set email alerts
|

Merging C–H Bond Activation, Alkyne Insertion, and Rearrangements by Rh(III)-Catalysis: Oxindole Synthesis from Nitroarenes and Alkynes

Abstract: We report a Rh­(III)-catalyzed ortho-C–H bond functionalization of nitroarenes with 1,2-diarylalkynes and carboxylic anhydrides. The reaction unpredictably affords 3,3-disubstituted oxindoles with the formal reduction of the nitro group under redox-neutral conditions. Besides good functional group tolerance, this transformation allows the preparation of oxindoles with a quaternary carbon stereocenter using nonsymmetrical 1,2-diarylalkynes. This protocol is facilitated by the use of a functionalized cyclopentad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…HRMS (ESI) m / z : [M + H] + calcd for C 20 H 16 NO 286.1232; found 286.1235. The analytical data are in accordance with the literature …”
Section: Experimental Sectionsupporting
confidence: 81%
See 2 more Smart Citations
“…HRMS (ESI) m / z : [M + H] + calcd for C 20 H 16 NO 286.1232; found 286.1235. The analytical data are in accordance with the literature …”
Section: Experimental Sectionsupporting
confidence: 81%
“…The analytical data are in accordance with the literature. 28 3,3-Diphenylindolin-2-one (1a). 28 Title compound was prepared with 3aa (43 mg, 0.12 mmol, 1 equiv) and TFA (37 μL, 48 mmol, 4 equiv).…”
Section: 3-diphenyl-2-(m-tolyloxy)-3h-indole (3aimentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, direct C–H activation functionalization of transition metal catalysts assisted by directed groups has been validated as a green synthetic approach for the rapid and efficient construction of diverse complex molecules . Transition metal catalysts such as Pd, Rh, Ir, and Ru are more active and more versatile. , In this research area, pioneers such as Yu, Glorius, Chang, and Ackermann have contributed tremendously to direct the C–H activation reaction. , In particular, Rh­(III)-catalyzed C–H functionalization reactions have become a high-efficiency and powerful tool in organic synthesis and medicinal chemistry for decades. , Until now, several N -oxide-containing functional groups such as quinolone N -oxides, nitrones, tertiary arylamine N -oxides, and nitroarenes have been used for direct C–H activation reactions (Scheme a). , However, only few studies have reported that the nitro group can act as an efficient directing group in Cp*Rh­(III)-catalyzed C–H bond activation reactions (Scheme b) . The reported reactions mainly include the Rh­(III)-catalyzed ortho-alkynylation of nitroarenes (Scheme b-1), cascading Rh­(III)-catalyzed C–H activation, alkyne insertion, and rearrangements to synthetic oxindole (Scheme b-2).…”
mentioning
confidence: 99%
“…Because of the powerful role of rhodium catalyst in amidation reactions, , an efficient diamidation reaction was realized when catalyzed by [Cp*RhCl 2 ] 2 under rather mild reaction conditions with Ag 2 O (0.1 equiv) as an additive (see Scheme and Table S1). With dioxazolone as the limiting reagent, diamidation product 5aa was isolated in 80% yield.…”
mentioning
confidence: 99%